The Book of Cuttings for Acting and Directing - Cassady Marshall (National Textbook Company, 1989)
This book offers a wide range of scenes for sharpening your theatre skills. Introduction, Monologues for Men, Monologues for Women, Cuttings for Two Women, Cuttings for Two Men, Cuttings for One Man and One Woman, Cuttings for Three Persons, Cuttings for Mixed Groups, Index.